The Current State of CSR Consultancy Development in Russia and the United Kingdom - Armley, Natasha (2005)
The research examines the phenomenon of corporate social responsibility (CSR) consultancy in Russia, as a new growing market, in comparison with well defined CSR consultancy in the UK, more advanced in CSR traditions and practices.